Gelombang Pengungsi Korea Utara di Korea Selatan: Politik Domestik, Integrasi dan Permasalahan Sosial - Vinesha Anindita (Universitas Airlangga, 2020)
This research attempts to analyze the wave of North Korean refugees toSouth Korea and how problems arise on the domestic political level to thesocietal level. Waves of refugees have occurred since the division of thetwo Koreas through the 38 parallel, which gave rise to defections fromNorth Korea. Meanwhile, South Korea is perceived as an ideal and safeplace to take shelter. This in turn raised numerous problems explicableby at least two theoretical frameworks, namely the world system theoryin explaining the desire to migrate, and the multiculturalist paradox,which explains the emergence of social and cultural frictions. Discourseon identity and social problems poses a challenge for the South Koreangovernment. On one hand, North Korean refugees can provide beneficialinformation for the government. On the other hand, two social problemsarise, namely the long-term problem for refugees in surviving the mentaland financial burdens, as well as the negative stigma and xenophobiaplaced by the South Korean society on the refugees. These are the reasonswhy integration remains difficult for refugees.